2004
DOI: 10.1074/jbc.m409174200
|View full text |Cite
|
Sign up to set email alerts
|

Non-proteolytic, Receptor/Ligand Interactions Associate Cellular Membrane Type-1 Matrix Metalloproteinase with the Complement Component C1q

Abstract: Matrix metalloproteinases (MMPs)1 constitute a family of zinc enzymes that are capable of cleaving a wide range of extracellular matrix proteins and soluble and cell surface-associated regulatory proteins (1). MT1-MMP, a prototypic member of a membrane-anchored MMP subfamily, is distinguished from soluble MMPs by the existence of a C-terminal transmembrane domain that associates the protease with the lipid membrane bilayer and a cytoplasmic tail that interacts with the intracellular milieu (2). Currently, six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 48 publications
1
13
0
2
Order By: Relevance
“…These sequence regions are spatially distant from the protease's active site. As a result, the catalytically active and the catalytically latent forms of cellular MT1-MMP are both efficient in binding with C1q [120]. In agreement, despite the MT1-MMP•C1q interactions, C1q is totally resistant to MT1-MMP proteolysis.…”
Section: Mt1-mmpsupporting
confidence: 58%
“…These sequence regions are spatially distant from the protease's active site. As a result, the catalytically active and the catalytically latent forms of cellular MT1-MMP are both efficient in binding with C1q [120]. In agreement, despite the MT1-MMP•C1q interactions, C1q is totally resistant to MT1-MMP proteolysis.…”
Section: Mt1-mmpsupporting
confidence: 58%
“…Several individual MMPs, including MMP-1, MMP-3, MMP-7, MMP-9, MMP-26, and MT1-MMP, have been reported to cleave AAT and to destroy its serpin activity (35)(36)(37)(38)(39)(40). The individual MMPs cleave 55-kDa AAT near the C terminus and generate the 51-kDa N-terminal fragment as well as a C-terminal fragment of ϳ4 kDa (38).…”
Section: Figure 3 Analysis Of Cellular Mt6-mmpmentioning
confidence: 99%
“…Our recent data suggested that MT1-MMP, in addition to its pericellular proteolytic function (18,19), protects malignant cells from complement-mediated cytotoxicity (20). We have also determined that the His 171 -Glu-Lys-Gln-Ala-Asp 176 and Val 223 -Arg-Asn 224 peptide sequences of the catalytic domain of MT1-MMP are directly involved in binding with the complement component C1q (21). Both sequence regions are spatially distant from the active site of MT1-MMP; therefore, whether active or inactive, the protease species efficiently bind but do not cleave C1q.…”
Section: Introductionmentioning
confidence: 96%